2007
DOI: 10.1111/j.1468-2370.2007.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities: A review and research agenda

Abstract: Metadata onlyThe notion of dynamic capabilities complements the premise of the resource-based view of the firm, and has injected new vigour into empirical research in the last decade. Nonetheless, several issues surrounding its conceptualization remain ambivalent. In light of empirical advancement, this paper aims to clarify the concept of dynamic capabilities, and then identify three component factors which reflect the common features of dynamic capabilities across firms and which may be adopted and further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,742
3
266

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,930 publications
(2,054 citation statements)
references
References 130 publications
(257 reference statements)
43
1,742
3
266
Order By: Relevance
“…Studies published in the last decade by Casslolato, Rosenberg, Castellacci, Fagerberg, Fagerberg, Maryann Feldman, Martin Srholec, showed that innovation is the engine of the growth, being an important element of the development achievements (Szabo, Šoltés & Herman, 2013). Innovation relies on the operations core competency of a firm (Ahmed & Wang, 2007). Innovations in relation to increasing of the business processes efficiency guarantee the strategic growth of the company and orienting management decisions to the position of knowledge represented by innovative products.…”
Section: Introductionmentioning
confidence: 99%
“…Studies published in the last decade by Casslolato, Rosenberg, Castellacci, Fagerberg, Fagerberg, Maryann Feldman, Martin Srholec, showed that innovation is the engine of the growth, being an important element of the development achievements (Szabo, Šoltés & Herman, 2013). Innovation relies on the operations core competency of a firm (Ahmed & Wang, 2007). Innovations in relation to increasing of the business processes efficiency guarantee the strategic growth of the company and orienting management decisions to the position of knowledge represented by innovative products.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have measured dynamic capabilities in different ways. Wang and Ahmed (2007) see adaptive capability, absorptive capability and innovative capabilities as dynamic capabilities. Li and Liu (2012) believe that dynamic capabilities include strategic sense-making capacity, timely decision-making capacity and change implementation capacity.…”
Section: Short-term and Long-term Capabilitiesmentioning
confidence: 99%
“…Most of technology based support tools for performance management and process improvement have been developed for enhancing control and 'upwards accountability ' [12] rather than preparing organizations for responsiveness by promoting learning, creativity and the enhancement of dynamic capabilities [13], [14].…”
Section: Business Process Management Systems and Process Improvemmentioning
confidence: 99%